Tindakan Pemerintah Thailand Dalam Merespons Gerakan Etnonasionalisme di Thailand Selatan Tahun 2004 – 2006. - Pramudita, Gede Richard; Fasisaka, Idin; Kawatri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 03 (2015), 2015)
ABSTACK Thailand is the  only country in Southeast Asia that had never been colonized. But Thailand was inseparable from the problem of the country’s internal conflict. The conflict happened between the Government of Thailand with a Muslim minority ethnic Malays in Southern Thailand. Conflict caused by ethno-nationalism movement which happened for a century and more drawn out. In southern Thailand, tension and violence occured every day. The conflict was capable considered  of threatening national security and forced the Thai government to take more serious action in response. This study aimed to describe the action taken by Thai government in response to ethno-nationalism movement in Southern Thailand in 2004 – 2006. The research method that used was  descriptive qualitative. Ethno-nationalism and coercive measures were the concept that  used to discuss this study. Keyword : Thailand, Conflict, Southern Thailand, Ethno-nationalism, Coercive measures.